ANALISIS FRAMING PEMBERITAAN GEMPA BUMI DI BALI PADA MEDIA ONLINE CNN INDONESIA DAN LIPUTAN6.COM - Ibrahim, Rima Maulani; Setiawan, Hendra (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to provide knowledge about the analysis of news framing in online media CNN Indonesia and Liputan6.com in reporting the Damage to Houses due to the Earthquake in Bali. In this framing analysis research using the approach of Zhongdang Pan and Gerald M. Kosicki. The method used in this research is descriptive qualitative method. The results of news analysis 1 and news analysis 2 have slightly different news titles, but the content conveyed is the same about the earthquake in Bali. The conclusion is in accordance with the theoretical analysis of Zhongdang Pan and Gerald M. Kosicki. News analysis 1 and news analysis 2 are: (1) There is a syntactic analysis, (2) Script Structure, (3) Thematic Structure, (4) Rhetorical structure. Keywords: Online Media, framing analysis, CNN Indonesia, Liputan6.com